KETERLIBATAN EMOSI SEBAGAI DASAR SUKSESI: STUDI PADA PERUSAHAAN KELUARGA MILIK PEREMPUAN - Kusuma, Gregoria Rosarheina (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
This study aims to examine the emotional involvement in the succession process of women-owned family companies. This qualitative research with a phenomenological approach examines 4 women-owned family companies that have succeeded in succession, and data were collected by semi-structured interviews. Research credibility is maintained by means of triangulation, member checking, and making descriptions of research results rich and concise. The results of the study indicate that there is an emotional bond between the owner and his company which is reflected in the company's basic values, the company's vision for the future, and the desire for the company to generate generations. In the succession process, this emotional bond is manifested in a distinctive way to select, train, and prepare children as heirs of the company. These typical ways support a succession process that feels